A metaheuristic for the capacity-pricing problem in the car rental business - Luis Filipe Ferreira Soares (2020)
The capacity-pricing problem in car rental has increasingly been stepping in the spotlight as companies began investing in advanced decision-support tools for these critical issues. When planning a sales period, a company must decide the number and type of vehicles needed in its fleet in order to meet demand. The demand for rental vehicles is particularly price-sensitive and therefore capacity and pricing decisions are closely linked. In addition, as the products are rented, the capacity "returns". This creates an association between capacity, fleet mobilization and other tools that allow the company to meet demand, such as upgrades, transferring vehicles between locations or the temporary leasing of additional vehicles. The impact of solving this complex problem on a company's profit has already been estimated and evaluated, but when real-world problems are taken into account, the size and complexity of the problem makes existing methods slow and inadequate to provide solutions within a reasonable time. Therefore, the main objective of this dissertation is then to select, design and develop an efficient metaheuristic that provides similar or better results than the ones obtained in the literature.